2020
DOI: 10.1007/s00268-020-05811-9
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Women Surgeons’ Careers in Low–Middle‐Income Countries: An International Survey

Abstract: Background Despite increasing numbers of women surgeons globally, barriers to career advancement persist. While these barriers have been extensively discussed in high-income countries (HICs), the topic has received minimal attention in lower-middle-income countries (LMICs) like Pakistan. Methods The Association of Women Surgeons of Pakistan (AWSP)-an organization in Pakistan consisting of female surgeons and trainees-carried out this international cross-sectional study over July-Sept 2019. An anonymous online … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 26 publications
3
24
0
Order By: Relevance
“…Overall, 27 papers92–118 were focused on careers for female surgeons, of which 12 were surveys, 5 were retrospective observational studies, 5 were cross-sectional studies and 5 were semi-structured interviews (Supplemental Material Table 3, Supplemental Digital Content 1, http://links.lww.com/SLA/D857). Of those, 15 were based in the United States, 3 in Canada, 1 in USA-Canada, 2 in Japan, 1 in Germany, 1 in Nigeria, 2 in Pakistan, 1 in Saudi Arabia, and 1 from the collaboration between Egypt, Jordan, and Saudi Arabia.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 27 papers92–118 were focused on careers for female surgeons, of which 12 were surveys, 5 were retrospective observational studies, 5 were cross-sectional studies and 5 were semi-structured interviews (Supplemental Material Table 3, Supplemental Digital Content 1, http://links.lww.com/SLA/D857). Of those, 15 were based in the United States, 3 in Canada, 1 in USA-Canada, 2 in Japan, 1 in Germany, 1 in Nigeria, 2 in Pakistan, 1 in Saudi Arabia, and 1 from the collaboration between Egypt, Jordan, and Saudi Arabia.…”
Section: Resultsmentioning
confidence: 99%
“…LMIC women shared more instances of blatant gender discrimination during these interactions than HIC women. Although we did not ask participants to stratify the most common sources of gender discrimination/bias, a prior study comparing the experiences of Pakistani female surgeons to HIC female surgeons found that the most common sources of gender bias/discrimination were coresidents (73.9%), consultants (73.9%), and nurses/OR staff (58.7%) 9 . Overall, our findings suggest that female otolaryngologists, regardless of career stage and setting, face significant microaggressions in their day‐to‐day interactions with patients and allied health staff.…”
Section: Discussionmentioning
confidence: 99%
“…Major themes previously identified in the literature on gender inequalities served as a basis for the interview questions. [3][4][5]9,[11][12][13] Table I illustrates the questions utilized in this study. Interviews were conducted via video teleconferencing.…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…In addition, given frequent occurrences of physical aggression from patients or attendants [ 17 ], particularly during the COVID-19 (coronavirus disease 2019) pandemic [ 18 , 19 ], many aspiring women surgeons in Pakistan are deterred from pursuing a surgical career due to the threat of aggressive behavior [ 20 ]. Even as surgical faculty, women in Pakistan still face hindrances to progression up the academic hierarchy, with sex-based biases in the workplace affecting most aspects of their careers, including promotion opportunities and access to leadership positions [ 11 ].…”
Section: Introductionmentioning
confidence: 99%